PERAN BARU SEBUAH SEKOLAH: MEMBERIKAN PENITIPAN ANAK DAN KELUARGA LAYANAN DUKUNGAN (SEBUAH REVIEW DALAM BUKU STENBERG) - Rheviana Dian Miranti; Eva Latipah (KOLONI, 2022)
Socio-cultural influences in this era bring various changes, one of which is a change in the function of a family. The number of working women has increased from the previous year, so childcare is something that needs to be considered, especially for mothers who are also breadwinners. Child care is an alternative in nurturing, caring for, protecting, and guiding children, especially child services entering the golden age. The method used in this study is a literature review which discusses sub-chapters with the theme of the new role of a school in Stenberg's book. The results of the review show that child care centers in influencing their development and growth depend on the quality of care, the programs carried out, and adequate infrastructure. Daycare can be a solution for busy working parents. In addition, daycare centers are also prepared to develop their potential so that children will be ready to enter the next stage of education. Because in preparation for the next stage of education, it is not only in the academic field but also in the social, emotional, and behavioral fields of children. Child care is a facility that is rich in stimulus and can optimize children's growth and development if there are several factors that play a role, such as knowledge of caregivers about child development, ratio of children to caregivers, and understanding of learning theory. Understanding the growth and development of children can help caregivers provide the right stimulus for the child. Then the ratio between children and caregivers, understanding of learning theory can also help optimize children's growth and development. So that parents do not need to worry or even worry about the process of child development if they leave it in a quality daycare center. Keywords: Child care, parents, child development.